Wunderlich′s syndrome and hemorrhagic shock - Medda Massimo (Journal of Emergencies, Trauma and Shock, 2009)
We report a case of Wunderlich′s syndrome in an obese woman associated with massive retroperitoneal hemorrhage. Stable hemodynamic patient condition was obtained by selective arterial embolization. Since the first embolization of a renal angiomyolipoma in 1976 by Moorhead et al., highly selective renal arterial embolization of angiomyolipoma with rupture has become a procedure that offers greater efficacy, particularly in life-threatening cases.